Global guideline for the diagnosis and management of rare yeast infections: an initiative of the ECMM in cooperation with ISHAM and ASM. Issue 12 (December 2021) - Chen, Sharon C-A; Perfect, John; Colombo, Arnaldo L; Cornely, Oliver A; Groll, Andreas H; Seidel, Danila; Albus, Kerstin; de Almedia, Joao N; Garcia-Effron, Guillermo; Gilroy, Nicole; Lass-Flörl, Cornelia; Ostrosky-Zeichner, Luis; et al.
Summary: Uncommon, or rare, yeast infections are on the rise given increasing numbers of patients who are immunocompromised or seriously ill. The major pathogens include those of the genera Geotrichum, Saprochaete, Magnusiomyces, and Trichosporon (ie, basidiomycetes) and Kodamaea, Malassezia, Pseudozyma (ie, now Moesziomyces or Dirkmeia ), Rhodotorula, Saccharomyces, and Sporobolomyces (ie, ascomycetes). A considered approach to the complex, multidisciplinary management of infections that are caused by these pathogens is essential to optimising patient outcomes; however, management guidelines are either region-specific or require updating. In alignment with the One World–One Guideline initiative to incorporate regional differences, experts from diverse geographical regions analysed publications describing the epidemiology and management of the previously mentioned rare yeasts. This guideline summarises the consensus recommendations with regards to the diagnostic and therapeutic options for patients with these rare yeast infections, with the intent of providing practical assistance in clinical decision making. Because there is less clinical experience of patients with rare yeast infections and studies on these patients were not randomised, nor were groups compared, most recommendations are not robust in their validation but represent insights by use of expert opinions and in-vitro susceptibility results. In this Review, we report the key features of the epidemiology, diagnosis, antifungal susceptibility, and treatment outcomes of patients with Geotrichum, Saprochaete, Magnusiomyces, and Trichosporon spp infections.